PENGUKURAN KINERJA KEUANGAN RETURN ON ASSETS (ROA) DAN RETURN ON EQUITY (ROE) BERDASARKAN PERUBAHAN LABA KOMPREHENSIF PADA PERUSAHAAN REASURANSI DI INDONESIA - Suhartono Suhartono; Reimond Hasangapan Mikkael Napitupulu; R.Muh Deddy Hanif Sardjito (JURNAL LENTERA BISNIS, 2023)
This research was conducted to find out the effect of Return On Equity and Return On Assets on Changes in Comprehensive Income of Reinsurance Companies in Indonesia. Secondary data was obtained from the company's financial statements listed on the official website and the Indonesia Stock Exchange (IDX) in 2011- 2020. The following research test uses multiple linear regression analysis method. The results of this study are: (1) partial test results (t), there is no effect of ROE on changes in comprehensive income. (2) partial test results (t), there is no effect of ROA on changes in comprehensive income. (3) simultaneous test results (f) namely the influence between ROE and ROA on changes in comprehensive income. Keywords: Return On Equity, Return On Assets, Changes in Comprehensive Income.